Penguatan Nilai-Nilai Moderasi Beragama Mahasiswa Melalui Mata Kuliah Al-Islam Kemuhammadiyahan - R. Nurhayati; Nur, A. Taufiq; Is, Sitti Satriani; Wulan, Sry; Urva, Magfira; Khaerati, Pasta Bikul (LP2M Universitas Islam Ahmad Dahlan, 2024)
Character of students who are starting to decline from Islamic values ​​requires action from educators so they need to strengthen religious moderation through AIK courses. The aims of this research are to describe: 1) the strategy for strengthening religious moderation education through the Muhammadiyah al-Islam course at the PAI UNISMUH Makassar Study Program, and 2) the obstacles faced in strengthening religious moderation education through the Muhammadiyah al-Islam course. The method used in this research is descriptive with a qualitative approach. This research was conducted during March-May 2024 at UNISMUH Makassar. Data collection techniques use observation and interviews. The subjects of this research were five people, including two lecturers who taught the Al-Islam Kemuhammadiyahan, Deputy Chancellor IV for AIK, and two students of PAI study program. The research results show that: 1) religious moderation is implemented by lecturers through several strategies, including strengthening neutral attitudes; fair attitude; strengthening the character of tolerance; deliberation; reform; pioneer; help each other; non-violence; and respect for culture. 2) The obstacle faced is diversity of understanding because the condition of the large population in universities produces a variety of individuals with different understandings, not all of whom agree with Muhammadiyah's understanding, some even hate Muhammadiyah.